2020
DOI: 10.1186/s43094-020-00144-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in silico studies and antibacterial activity of some novel 2-substituted benzimidazole derivatives

Abstract: Background The o-phenylenediamine is a versatile starting material for several compounds. Synthesized o-phenylenediamine and amino acids (glycine, alanine, aspartic acid, and l-proline) undergo condensation via Phillips reaction. The synthesized compound showed the promising antibacterial activity of Bacillus subtilis and Pseudomonas aeruginosa at the concentration of 100, 50, 25, 12.5, 6.25, 3.12, 1.6, 0.8, 0.4, and 0.2 μg/ml. Ciprofloxacin was used as standard drug. Synthesis of benzimidazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…These compounds have a common benzimidazole nucleus present in several approved drugs, most of them substituted at position 2 [29] as shown in compounds 1 and 2. Other 2-substituted benzimidazole derivatives have also shown activity as analgesics, anti-inflammatory [30] and antibacterial agents [31]. Furthermore, docking studies showed that 2, 5 (6) substituted benzimidazole derivatives are also molecules with potential as antimicrobial agents [32].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have a common benzimidazole nucleus present in several approved drugs, most of them substituted at position 2 [29] as shown in compounds 1 and 2. Other 2-substituted benzimidazole derivatives have also shown activity as analgesics, anti-inflammatory [30] and antibacterial agents [31]. Furthermore, docking studies showed that 2, 5 (6) substituted benzimidazole derivatives are also molecules with potential as antimicrobial agents [32].…”
Section: Discussionmentioning
confidence: 99%
“…O ‐phenylenediamine (5 mmol) and various amino acids (7 mmol) reacted together to yield 1‐(1 H ‐ benzimidazol‐2‐yl)‐substituted amine ( 2 ) as per the reported protocol and also the melting point was observed of the reported intermediates [28–30] …”
Section: Methodsmentioning
confidence: 96%
“…O-phenylenediamine (5 mmol) and various amino acids (7 mmol) reacted together to yield 1-(1H-benzimidazol-2-yl)-substituted amine ( 2) as per the reported protocol and also the melting point was observed of the reported intermediates. [28][29][30] General steps for synthesis of The usual treatments in scPTZ models were carbamazepine and phenytoin sodium. During the scPTZ screening, pentylenetetrazol (PTZ) was delivered to albino mice to induce convulsions.…”
Section: Synthesis Of Substituted 1-(1h-benzimidazol-2-yl)methenamine...mentioning
confidence: 99%
“…Benzimidazole is also one of the frequent heterocycles in pharmaceuticals. Therefore, we became interested in exploring the construction of a novel hybrid skeleton, N -fused benzimidazo-β-carboline . To the best of our knowledge, there are only two methods known in the literature toward the synthesis of benzimidazo-β-carbolines with limited examples.…”
Section: Introductionmentioning
confidence: 99%